Analysis of Organizational Culture in Enhancing Employee Performance at the Public Relations Bureau of the Secretariat General of the Ministry of Defense of the Republic of Indonesian - Azisah, Afifah Nur; Prathama, Ananta (ARISTO, 2025)
Organizational culture plays an important role in the success of public organizations and can help align human resources in achieving the organization's vision, mission, and goals. This study aims to analyze the organizational culture at the Public Relations Bureau of the Secretariat General of the Ministry of Defense of the Republic of Indonesia (Setjen Kemhan RI) and explain how organizational culture can deeply enhance employee performance. This research uses a qualitative approach with descriptive analysis techniques. Data collection was conducted through in-depth interviews, direct observation, and documentation. The research results indicate that the organizational culture at the Public Relations Bureau of Setjen Kemhan RI has successfully improved employee performance. Indicators such as the produced products, ethics or professionalism standards, and attributes that reflect the identity of the Public Relations Bureau of Setjen Kemhan RI have been well implemented. Employees of the Public Relations Bureau of Setjen Kemhan RI have successfully applied the values embraced by the institution, which positively influence their performance. The public has been satisfied with the products and services provided, although there is still a lack of information and understanding among the public regarding exempted information.